Study on a new process and its kinetics of iron recovery and glass-ceramics preparation from desulfurization slag - Tong, Zhibo; Sun, Jingting; Liu, ShiChang; Zhang, Wei; Kuang, MeiLing (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
This paper creatively proposes a new process with desulfurization slag leached by ammonium chloride as pretreatment, and the main point of this paper lies in the processing of desulfurization residue leached by ammonium chloride. Through component analysis the formula is adjusted with high aluminum coal ash and glass cullet, making the melting point of the reduction slag around 1200 ℃, which facilitates the separation of iron and slag At the same time, the reduction slag is adjusted to the target crystallization phase, so that the high temperature reduction slag after carbon thermal reduction can be used to produce glass-ceramics directly. The results show that iron recovery rate is over 99%, and diopside and nepheline glass-ceramics are produced, which shows that the new process is feasible. However, the crystal growth index is less than 3, which means that the crystallization capacity of the glass-ceramics is low, and nucleating agent is needed in the preparation of glass-ceramics.
Keywords: Desulfurization slag; Glass-ceramics; Diopside and nepheline; Kinetics; Factsage